Thalassemia and its management – A review article - Neha Kansal (International Journal of Tropical Medicines, 2024)
Thalassemia is a hemoglobinopathy burdening India making it earn title of Thalassemia capital of world. Studying last decade, the overall prevalence worldwide and incidence rates have declined but prevalence rates were high in east and Southeast Asian countries. Screening for carriers and affected individuals and genetic counselling are promising approaches for reducing soaring cases and reducing the further spread. Thalassemia affects various organs due to iron overload and haemolysis leading to cascade of complications ranging from physical deformities to fatal outcomes like heart failure. Continuous monitoring of is requires with multidisciplinary approach to handle the adverse reactions of treatment modalities and deal with complications. The treatment of Thalassemia ranges from conventional blood transfusions and chelation therapy to curative i.e. bone marrow transplant and gene editing and newer drugs targeting ineffective erythropoiesis and production of foetal haemoglobin. Chronic nature of the disease affecting quality of life of children makes nurses teaching them self-care management techniques more essential. Role of nursing strategies for managing thalassaemic children is through holistic approach which is addressing their developmental needs as per their age. Various governmental and NGO initiatives and programmes have made a significant impact but multisectoral approach is needed to tackle the emerging cases.
Keywords: Bone Marrow Transplant; Genetic Screening; Quality of life; Self-care; Thalassemia